Reinterpretation Of The Eight Groups Of Zakat Recipients: Special Issue On Fakir Miskin And Fi Sabilillah Dealing With The Impact Of Covid-19 In Indonesia - Hakim, Rahmad; Noviyanti, Ririn (Univeristas Islam Bandung, 2022)
The COVID-19 pandemic has resulted in several negative socio-economic impacts, including an increase in poverty rates and also a high level of exposure to and deaths cases. This paper aims to conduct an in-depth analysis related to dinamism in the interpretation of the recipient group of zakat (asnaf tsamaniyah) to solve the socio-economics problem caused by covid-19 in Indonesia. This study was qualitative with documentation as method of collecting data, the data analysed by content analysis approach by Miles and Huberman. The result found that dinamism in the interpretation of the recipient group of zakat to solve the socio-economics problem caused by covid-19 in Indonesia laid down by focusing on the poor and needy (fakir miskin) than other group of zakah recipient because the increase of poverty levels due to high dismissals and declining levels of public purchasing which caused to bankrupt. On the other hand, there is a new interpretation based on the fatwa of the Indonesian Ulema Council, that the allocation of zakat funds for the need for personal protective equipment for the prevention of Covid-19 such as hand-sanitizers and masks can be included in the category of recipients of zakat funds fi sabilillah.